Understanding the 24-Hour City: Engagement, Positionality, and the Coproduction of Knowledge. Issue 2 (3rd April 2018) - Glass, Michael
Abstract : This article explores the production of geographic knowledge arising through civic engagement, using the example of a research course in Pittsburgh's South Side Flats neighborhood. Although civic engagement is a persistent feature in geography research and education, recent papers note that the term civic engagement conceals diverse practices and goals and that the outcomes of engagement are usually uncertain. In this article, I argue that attention must be paid to the positionality of stakeholder groups at all stages of the engagement process and that there are necessary limits to how participatory the coproduction of knowledge can be during a civic engagement course.